Work Life Balance As A Moderating Variable On The Influence Of The Green Organizational Culture Variable On Employee Performance - Budi Sulistyo Nugroho; Teguh Setiawan Wibowo; Subawa Subawa; Farid Alfalaki Hamid; Arif Nurrahman (UNIVED Press, 2024)
This research is quantitative research with an exploratory approach, an approach that uses previous research as the main foundation pillar for building the article's argumentation building. The data used in this research is primary data obtained from PTPN employees spread throughout Indonesia from Sumatra to Papua. The amount of data obtained was 500 data from the 500 employees. The questionnaire contains 5 statements, namely strongly agree, agree, normal/so-so, disagree, and strongly disagree. These data were analyzed using the Smart PLS 4.0 analysis tool.